2016
DOI: 10.1016/j.ultramic.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Large volume serial section tomography by Xe Plasma FIB dual beam microscopy

Abstract: Ga(+) Focused Ion Beam-Scanning Electron Microscopes (FIB-SEM) have revolutionised the level of microstructural information that can be recovered in 3D by block face serial section tomography (SST), as well as enabling the site-specific removal of smaller regions for subsequent transmission electron microscope (TEM) examination. However, Ga(+) FIB material removal rates limit the volumes and depths that can be probed to dimensions in the tens of microns range. Emerging Xe(+) Plasma Focused Ion Beam-Scanning El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
164
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 278 publications
(166 citation statements)
references
References 44 publications
1
164
1
Order By: Relevance
“…These results are consistent with the similar study of leaching behaviour of SAPP in the coating, which showed a much higher dissolution rate of strontium‐rich particles comparing with aluminium‐rich particles (Emad et al ., , Liu et al ., ). The bias and variance of the nano‐CT measurements were estimated using the SIMEX technique (Bradley, ). It was found that noise in the scan data led to the volume fractions being underestimated (negatively biased) by a relatively small amount (<0.5%), although the standard deviations were estimated to be much smaller at <0.01%.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with the similar study of leaching behaviour of SAPP in the coating, which showed a much higher dissolution rate of strontium‐rich particles comparing with aluminium‐rich particles (Emad et al ., , Liu et al ., ). The bias and variance of the nano‐CT measurements were estimated using the SIMEX technique (Bradley, ). It was found that noise in the scan data led to the volume fractions being underestimated (negatively biased) by a relatively small amount (<0.5%), although the standard deviations were estimated to be much smaller at <0.01%.…”
Section: Resultsmentioning
confidence: 99%
“…Nano-tomography applied through the use of FIB-SEM microscopes is a powerful analytical tool that is being increasingly applied to biological [81], material [82,83], and geological problems [37,[84][85][86][87]. Specifically, the integration of FIB capabilities into a typical SEM allows for the removal of material with a high spatial control and precision to generate images of the freshly exposed material in situ within minutes.…”
Section: Discussionmentioning
confidence: 99%
“…volume we were able to enclose from shot peened sub-micron size grains regions down to the based material. A new version (1.6) of the FEI Slice and View TM software which incorporates a rocking polish (described in details in [58]) into an automated routine was used for the SST. A block of 100 × 66 × 30 μm 3 on the shot peneed surface of sample with 2 mm radius notch was sectioned.…”
Section: Methodsmentioning
confidence: 99%